Ground Characterization and Foundations Proceedings of Indian Geotechnical Conference 2020 Volume 1 - Satyanarayana Reddy, C. N. V.; Muthukkumaran, K.; Satyam, Neelima; Vaidya, Ravikiran; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book comprises the select proceedings of the Indian Geotechnical Conference (IGC) 2020. The contents focus on recent developments in geotechnical engineering for a sustainable tomorrow. The book covers the topics related to traditional and latest methods in characterisation of ground at construction sites, recent technological developments/ advances in design of shallow and deep foundations in different subsoil conditions.
Effect of Plasticity of Fines on Properties of Uniformly Graded Fine Sand -- Comparison of Theoretical and Laboratory Permeability for Coarse Grained Soil at Different Ground Conditions -- Durability Study on Coir Fiber Reinforced Soil -- Re-evaluation of Failure of Silo Tower Foundations -- Engineering Performance of the Foundation of Thanjavur Brihadeeswarar Temple -- Analytical Study of Load Carrying Capacity of Fiber Reinforced Polymer Piles -- Instrumented Pile Load Tests in Southern India.
Keywords: Engineering geology; Building materials; Geotechnical engineering; Geoengineering; Building Materials; Geotechnical Engineering and Applied Earth Sciences; Earthwork -- Congresses; Foundations -- Congresses